Tra legge, corpo e simbolo. La paternità omosessuale e la cultura androcentrica in Sei come sei di Melania G. Mazzucco - Kornacka, Barbara (Romanica Silesiana)
The following paper analyzes the theme of homosexual paternity. It analyzes Mazzucco’s novel on three different levels: the legal and social context, the gender perspective, and the level of literary and artistic symbols. In each of these areas we can observe the importance given to traditional paternity, seen as legal power or divine creation of the men. On the contrary, homosexual paternity is excluded by law, denied as containing maternal elements, and endowed with modest symbolic power.